Pembelajaran lifeskill dan prestasi belajar sebagai pendorong minat berwirausaha - Dharmosamoedero, Djati Poetryono (JURNAL TALENTA PSIKOLOGI, 2015)
Enterpreneurship is a supporting factor that determines the reciprocation of the economy of a country. for college graduates be given with knowledge and skills should dare to create their own jobs to take advantage of its knowledfe and skills in accordance with their respective fields. by teaches enterpreneurship at each vocational field, the students are expected after graduation us abke to develop the business world to create their own jobs in accordance with their skills, thus the interest in enterpreneurship in students need is grown. interest in enterpreneurship include : willingness to work hard and dilligently to achieve its business pregress, the willingness to bear various risks associated with the action sought is doing willing to take the path and a new way, a willingness to live frugally, a willingness to learn from failures. the abillity of exsisting skills and learning achievement that will either be able to create an interest in enterpreneurship.